REESTRUTURAÇÃO DO SETOR DE GERENCIAMENTO DE PROJETOS EM UMA INDÚSTRIA DE CONFECÇÃO: RESTRUCTURING OF THE PROJECT MANAGEMENT SECTOR IN A CLOTHING INDUSTRY - Lavezo dos Reis, Beatriz; Ana Carla; Lapasini Leal, Gislaine Camila; Meurer da Silva, Marcos (Brazilian Journal of Production Engineering, 2020)
The competitive scenario requires from organizations a differential to stand out before competitors and, in this context, project management can be seen as one of the success factors. In order to manage the projects of a company, structuring and organization of a team is necessary, responsible for enabling planning, execution and control of projects, integrating several areas and their stakeholders. Thus, this article aims to restructure the project management sector in a clothing industry. From a study of project sector current situation in industry in question, an organizational structure was proposed for project office, with elaboration of a new organization chart. In addition, a methodology for project management was developed, as well as the partial application of it in a pilot. From results obtained, it is concluded that the work presents great importance in industry and also for academic community, through development of a hybrid methodology of project management.